The Influence of Confining Topography Orientation on Experimental Turbidity Currents and Geological Implications - Soutter, Euan L.; Bell, Daniel; Cumberpatch, Zoë A.; Ferguson, Ross A.; Spychala, Yvonne T.; Kane, Ian A.; Eggenhuisen, Joris T. (Frontiers in Earth Science, 2021)
Turbidity currents distribute sediment across the seafloor, forming important archives of tectonic and climatic change on the Earth’s surface. Turbidity current deposition is affected by seafloor topography, therefore understanding the interaction of turbidity currents with topography increases our ability to interpret tectonic and climatic change from the stratigraphic record. Here, using Shields-scaled physical models of turbidity currents, we aim to better constrain the effect of confining topography on turbidity current deposition and erosion. The subaqueous topography consists of an erodible barrier orientated 1) parallel, 2) oblique and 3) perpendicular to the incoming flow. An unconfined control run generated a supercritical turbidity current that decelerated across the slope, forming a lobate deposit that thickened basinwards before abruptly thinning. Flow-parallel confinement resulted in erosion of the barrier by the flow, enhanced axial velocities, and generated a deposit that extended farther into the basin than when unconfined. Oblique confinement caused partial deflection and acceleration of the flow along the barrier, which resulted in a deposit that bifurcated around the barrier. Forced deceleration at the barrier resulted in thickened deposition on the slope. Frontal confinement resulted in onlap and lateral spreading at the barrier, along with erosion of the barrier and down-dip overspill that formed a deposit deeper in the basin. Acceleration down the back of the barrier by this overspill resulted in the generation of a plunge-pool at the foot of the barrier as the flow impacted the slope substrate. Observations from ancient and modern turbidity current systems can be explained by our physical models, such as: the deposition of thick sandstones upstream of topography, the deposition of thin sandstones high on confining slopes, and the complex variety of stacking patterns produced by confinement. These models also highlight the impact of flow criticality on confined turbidity currents, with topographically-forced transitions between supercritical and subcritical flow conditions suggested to impact the depositional patterns of these flows.